Discrepancies Between Quarterly GDP Estimates - Bloem, Adriaan (IMF Working Papers; Working Paper ;, 1997)
Countries compiling quarterly estimates for gross domestic product (GDP) often use alternative approaches simultaneously. This may result in the publication of different measures of quarterly GDP and discrepancies between these measures. Such discrepancies are unavoidable, unless reconciliation takes place or the measures are mutually interdependent. This paper examines international practices in this respect, focusing on OECD member countries that publish quarterly GDP data. Of these, five publish GDP data with discrepancies-the United States, the United Kingdom, Canada, Australia, and New Zealand-and the paper examines causes and the development of these discrepancies.